Life cycle assessment and emission analysis of waste cooking oil biodiesel blend and fossil diesel used in a power generator. (1st December 2020) - Viornery-Portillo, Emilio A.; Bravo-Díaz, Brenda; Mena-Cervantes, Violeta Y.
Graphical abstract: Highlights: Comparative LCA of WCO-B25 blend and ULSD in diesel power generator was performed. WCO-B25 blend outperformed ULSD in all LCA impact categories. Main contribution to environmental impacts was related to production of ULSD. Engine parameters should be considered in order to maximize environmental benefits. Abstract: The environmental impact of biodiesel production from waste cooking oil has been previously evaluated through life cycle assessment and, in all cases, it presents a lower ecological burden compared to first and third-generation biodiesel. However, production-use studies are scarce, particularly in the case of biodiesel consumption for power generation, at large and reduced scale. Thus, there is high uncertainty as to the combined contribution of the production process and exhaust emissions to the overall environmental footprint of biodiesel. This work performs a comparative analysis of the environmental impacts associated with the production and use of B25 biodiesel blend and ultra-low sulphur diesel in a power generator of 33 kW, at 100% of rated load and using life cycle methodology to characterise the derived impacts, based on primary data for process and use stages. The results of the modelling showed that B25 outperforms ultra-low sulphur diesel in all categories. Major impact reductions were found for abiotic depletion, potential for human toxicity, eutrophication potential, acidification potential, and global warming potential categories with 39.48%, 39.44%, 39.24%, 38.73%, and 35.77% respectively. Experimental measurement of exhaust emissions showed an increase in CO (52%) and a decrease in NOx (41.54%) for B25, compared to ultra-low sulphur diesel. The overall results indicate that the use of biodiesel blends in power generators could offer important environmental benefits from a life cycle perspective. However, a careful evaluation of engine specifications must be carried out when higher biodiesel blends are used, in order to maximise these benefits.